The role of moral disengagement of teachers in the face of cyberbullying: Challenges for training - Ferreira, Paula (2023)
Cyberbullying is one of the major challenges teachers face in their professional practice and has a significant impact on students' well‐being. Moral disengagement plays a crucial role in this phenomenon, as it refers to socio‐cognitive mechanisms individuals use to justify morally reprehensible conduct. This study aims to explore the mechanisms of moral disengagement present in teachers' discourse regarding cyberbullying situations and understand their role in dealing with these situations. Sixty‐three individual and semi‐structured interviews were conducted with teachers from the 3rd cycle of basic education in the Portuguese context. Content analysis results reveal that teachers primarily use displacement and diffusion of responsibility. Additionally, teachers attribute seriousness to these situations and acknowledge their negative impact on victims. Despite employing these mechanisms, teachers perceive themselves as having an important role in intervention; however, they need tobecome aware of how they use these mechanisms and their negative impact on resolution. These findings underscore the need to develop teacher training programs focused on the role of moral disengagement in how teachers deal with cyberbullying situations.